Sowing the Seeds of Sustainability : A Case Project with Unifrutti, IFC, and Smallholder Banana Farmers in the Philippines - Macawaris, Natalie; Taylor, Colin; Zamora-Galinato, Carla (World Bank, Washington, DC, 2012)
Smallholder banana farmers are beginning to understand that their old farming methods are contributing to the planet's drying up or suffocating in fields of garbage. They are convinced that they have to change their ways for the good of their farms, their communities, and their children. But what really drives them to adopt new and sustainable practices? What will ensure they continue to do so? International Finance Corporation (IFC) partnered with Unifrutti Philippines in 2008 to work with farmers to enable them to be certified to the international Sustainable Agriculture Network standards of the Rainforest Alliance (RA). With concerted efforts from Unifrutti (the lead firm) and IFC, smallholder farmers were trained to understand the RA standards and auditing processes, buy into the concepts of environment and social sustainability, adopt new sustainable practices, and pass the certification audit all within 12 months. This smart lesson examines the difficult challenges of instituting change, as well as the necessary steps to ensure ongoing sustainability.